Synthesis and Characterization of Polymer Particles as Metal‐Free Catalysts for Electrooxidation and Methanolysis of Sodium Borohydride - Gokkus, Kutalmis; Kaya, Sefika; Yildiz, Derya; Saka, Ceren; Gür, Mahmut; Bütün, Vural; Kivrak, Hilal (Wiley, 2024)
Abstract In this study, trimethylolpropane triglycidyl ether/diethylenetriamine (TD) and glutaraldehyde/diethylenetriamine (GD) polymer particles are synthesized as catalysts for hydrogen production from NaBH 4 methanolysis and NaBH 4 electrooxidation. SEM, FT‐IR and TGA characterization methods are applied to determine the surface morphologies, chemical structures, thermal stability and decomposition of the synthesized polymer particles. The parameters affecting the hydrogen generation rate on NaBH 4 methanolysis are investigated and optimum conditions are determined. Under optimum conditions, the hydrogen generation rates of TD and GD polymer particles are obtained as 34903.2 and 97998 mL/min.g cat , respectively. The activation energies of TD and GD polymer particles are also calculated as 16.86 and 18.14 kJ/mol, respectively. The catalytic activities of polymer particles as anode catalysts in NaBH 4 electrooxidation are determined by CV, CA, EIS analyses. The specific activities of TD and GD polymer particles are acquired as 0.54 and 0.64 mA/cm 2 , respectively. These results indicate that the synthesized polymer particles are promising catalysts for electrooxidation and methanolysis of sodium borohydride.